Grammatical Features of the Names of Uzbek National Sweets - Shukhratovna, Kholova Shahnoza (Miasto Przyszłości, 2023)
In this article, specific features of dessert names are analyzed from a linguistic point of view. There are studied morphological and syntactic qualities of the grammatical aspects. It should be noted that the grammatical features reflected in the names of sweets are determined by how they are used in syntactic structures. Recap. Morphological and syntactic features in the names of Uzbek national sweets.